Assessment of Urban Heritage Potential and Flood Resilience in the Colonial Tourism Area of Cirebon City: A Case Study of Lemahwungkuk Subdistrict - Rochmat Hadi Sumitro; Chika Trisna Dewi; Mohd. Abi Rafdi (Riviera Publishing, 2025)
Cirebon is a coastal city rich in cultural heritage, particularly colonial-era buildings documented since the 15th century. Despite this historical wealth, no Regional Regulation specifically governs the management of strategic colonial heritage areas. The absence of such regulation leaves these sites vulnerable to damage from urban development and disasters, especially floods. This study aims to identify the potential of colonial heritage in Lemahwungkuk District for tourism while ensuring resilience to flooding. Using a mixed-methods approach, descriptive statistical analysis was applied through building observation with spider web graphs, combined with flood potential modeling using geospatial analysis to map vulnerability levels. The findings were triangulated with expert interviews. Results revealed that many heritage buildings are located in areas of very high flood risk, influenced by low soil permeability, dense building structures, and proximity to the Kriyan and Sipadu rivers. Observations also showed several buildings in poor condition, abandoned, or heavily damaged, increasing vulnerability. For development into a sustainable tourist area, further studies are required to assess flood and structural risks comprehensively. This should be supported by cross-sectoral coordination and improved drainage infrastructure to protect cultural assets.